L'art des funambules: les albums pour tous des Éditions Ipomée - L. Beckett, Sandra (Ondina - Ondine, 2020)
The important role that Éditions Ipomée played in the renaissance of children’s publishing in France beginning in the 1970s has been acknowledged. However, their books also made a significant contribution to what has come to be known in the Anglo-Saxon world as “crossover” literature. Books for all ages have existed for centuries, but it was only in the late 1990s that we began to talk about the crossover phenomenon. At first, there was a tendency to reserve the term for novels and to ignore picture books and illustrated books, although the latter, more than any other genre, are able to address all ages. Already in the 1970s, Éditions Ipomée, along with a few other innovative publishers, brought out picture books that challenged the conventions and traditional codes of children’s literature and offered readers true crossover picturebooks. This article pays homage to Éditions Ipomée and all their collaborators, so many “tightrope walkers”, who managed to balance on the tightrope stretched over the gulf between children’s literature and adult literature.Key words : crossover, books for all ages, Éditions Ipomée, picture books/picturebooks, illustration.